Construction project leadership from the perspective of Islam - Muhamad Rosdi Senam,; Khairuddin Abdul Rashid,; Azila Ahmad Sarkawi,; Rapiah Mohd. Zaini, (Universiti Kebangsaan Malaysia, 2014)
Construction industry is continuously being accused with common issues such as low performance, corruptions, spillages, bad practices in addition to common project failures despite advances in project management tools and techniques. This further adds to the existing and increasing complex and multi-facets business environment in construction projects that has resulted in the increasing pressure and challenges faced by project leaders and project managers today. Researchers in project management literature calls for more project leadership research as leadership now is increasingly recognised as project success factor. Ethical dilemma and leadership crisis facing the project managers and business organisations reveals the shortcomings and inadequacies of the conventional non-Islamic leadership that is believed to be or that has not fully considered the religious, spiritual, moral and ethical dimensions. Examples of these theories of leadership are authentic leadership, servant leadership and ethical leadership. Therefore, recent trend from literature has implicitly suggested a new form of leadership for construction project manager which is spiritual, moral, values and ethical form of leadership. The uniqueness of Islam is that it does not separate religion and other aspects of human life activities. Construction and project activities are part of the whole economic and social transactions of a nation and thus it is part of Islam. Project management in particular leadership awaits divine intervention that is tied to God consciousness and accords with values and principles prescribed in the Quran and Sunnah. This research is intended to overcome the spiritual and religious shortcomings of the present leadership models by proposing an Islamic perspective of leadership for construction project manager.